Preparation method of starch-based film with excellent mechanical property and pH responsiveness

By introducing cellulose nanofiber fibrils into starch-based films to immobilize prolanase and curcumin, the problem of the existing fully degraded plastic films lacking intelligent response capabilities is solved, and the mechanical performance improvement and intelligent monitoring functions of starch films are achieved.

CN119529338APending Publication Date: 2025-02-28TIANJIN UNIV OF SCI & TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411507870.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing fully degraded plastic film lacks intelligent response capabilities in food packaging and cannot monitor food freshness and degree of corruption in real time.

Method used

Cellulose nanofiber immobilized prolulanase and curcumin as key components were used to prepare starch-based films with excellent mechanical properties and pH responsiveness through extrusion treatment, preparation of pectin solution, preparation of cellulose nanofiber immobilized prolanase and preparation of curcumin-containing starch liquid.

Benefits of technology

It has achieved the mechanical performance improvement and intelligent response capabilities of starch films, and can change color according to environmental pH changes, thereby monitoring the freshness and degree of rot in real time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529338A_ABST
    Figure CN119529338A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a starch-based film with excellent mechanical property and pH responsiveness, and belongs to the technical field of food storage. Cellulose nanofibril immobilized pullulanase is introduced to significantly enhance the mechanical property and barrier property of the starch film, and a curcumin pH sensitive natural pigment is added to significantly enhance the barrier property of the starch film. The starch film can change color according to the change of the pH value of the environment, so that the intelligent response capability of monitoring the freshness and the putrefaction degree of the food in real time is realized. The color of the starch film can be obviously changed from white transparent to yellow transparent, and the tensile strength, the contact angle and the maximum degradation temperature are respectively improved from 9.29 MPa, 66.3 DEG C and 314 DEG C to 13.41 MPa, 87.2 DEG C and 340.5 DEG C. The barrier property is also improved, and the barrier property is reduced from 6.23 * 10 <-12 > g.cm / Pa.s.cm < 2 > to 4.78 * 10 <-12 > g.cm / cm < 2 >. Pa.s. The sensitive reaction capability to ammonia water with different concentrations can generate obvious color change. Considering the anti-oxidation characteristic of curcumin, the composite film has a potential pork fresh-keeping effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of food storage, and in particular to a method for preparing a starch-based film with excellent mechanical properties and pH responsiveness. Background Art

[0002] While synthetic polymer materials bring great convenience to people's lives, they also cause pollution to the environment. In addition, the oil reserves for making traditional plastics are constantly decreasing. Therefore, renewable and environmentally friendly natural polymer materials have become a research hotspot. Cellulose, starch, protein, etc. are the natural polymers that are currently being studied and applied more. Therefore, natural polymer-type fully degradable materials have become one of the research hotspots of new environmentally friendly materials.

[0003] Natural polymers have attracted widespread attention in food packaging and mulch film applications due to their wide availability, strong biodegradability, and excellent film-forming properties. However, inherent limitations of natural polymers, such as poor processing properties, brittleness, and water resistance, limit their application. Single modification methods such as plasticization, acidification, crosslinking, filling, or blending are often used to address this issue. However, these single modification methods are limited, resulting in limited functionality and high costs for the resulting fully biodegradable plastic films, making industrial production unfeasible.

[0004] Existing fully biodegradable plastic films do not have the intelligent response capabilities to monitor the freshness and degree of spoilage of food in real time. Summary of the Invention

[0005] The present invention aims to solve the above technical problems and provide a method for preparing a starch-based film with excellent mechanical properties and pH responsiveness.

[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0007] A method for preparing a starch-based film with excellent mechanical properties and pH responsiveness comprises the following steps:

[0008] S1. Extrusion treatment:

[0009] The absolute dry starch was mixed evenly using a material mixer, which was divided into five heating zones, namely 50°C, 65°C, 85°C, 100°C and 95°C. The extruded product was immediately freeze-dried and then crushed and sieved for later use;

[0010] S2. Preparation of pectin solution:

[0011] Prepare a standard solution with a pectin content of 60 mg / mL, add distilled water to make up to 100 mL, add 5.0 mL of sulfuric acid / sodium tetraborate solution after ice bath treatment, vortex mix thoroughly, heat in a boiling water bath, and cool to room temperature to obtain a pectin solution;

[0012] S3. Preparation of cellulose nanofibril-immobilized pullulanase:

[0013] CNF (1.0%-10% of the mass of absolute dry starch) and pullulanase (1U-10U per gram of absolute dry starch) are mixed, and the mixture is adjusted to pH 6 using phosphate buffer. The pH-adjusted mixture is shaken at a constant speed of 100-300 rpm in a constant temperature air bath shaker at 30°C for 1-3 hours to complete the immobilization of pullulanase on the cellulose nanofibrils, thereby obtaining a Pul@CNF complex.

[0014] S4, preparation of curcumin-containing starch solution:

[0015] Add 10 ml of 95% ethanol solution to each beaker, add 1-9% curcumin powder, and stir slowly with a glass rod to uniformly disperse the curcumin in the ethanol to obtain a curcumin-ethanol solution;

[0016] S5. Cellulose nanofibril immobilized pullulanase system enzymatically decomposes starch and adds tannic acid:

[0017] Take the absolutely dry starch in S1 and place it in a 250ml three-necked flask or round-bottom flask, add 50ml of distilled water to the flask, and place the flask in a 38℃ water bath. Stir slowly to fully disperse the starch and continue stirring for 5 minutes. Add the prepared Pul@CNF and pectin solution to the dispersed starch solution, and add water to a total volume of 100ml. Add the prepared curcumin-ethanol solution to the above solution respectively, continue stirring for 10 minutes, and heat to 95℃ at a rate of 1℃ / min. When the temperature When the temperature reaches 95°C, glycerol accounting for 40% of the absolute dry starch mass is added to the solution, and the solution is kept warm for 30 minutes while stirring. After the stirring is completed, the bubbles are removed from the obtained starch solution, and the starch solution is evenly spread onto an acrylic plate by a casting method. The acrylic plate with the starch solution spread is placed in a 50°C oven and dried for 8 hours to obtain a composite starch film containing curcumin. After drying, the composite starch film is torn off from the acrylic plate and stored at a temperature of 25°C and a relative humidity of 50% for 48 hours for subsequent use.

[0018] Preferably, the feed rate of the material mixer is 5-15 kg / h, and the screw speed is 10-20 rpm.

[0019] Preferably, the mass ratio of the pectin solution to the composite starch film is 1:9.

[0020] Preferably, the pectin is one or more combinations of xanthan gum, guar gum and sodium carboxymethyl cellulose.

[0021] Preferably, the product obtained by extrusion in step S1 is immediately freeze-dried and then crushed and sieved to 80-100 mesh for later use.

[0022] Preferably, in step S2, the mixture is vortex-mixed and then heated in a boiling water bath for 8-12 minutes.

[0023] Preferably, in step S1, the absolutely dry starch enters the five heating zones of the material mixer in sequence, and the mixing times are 5 min, 6 min, 4 min, 3 min and 3 min.

[0024] Preferably, the tensile strength of the composite starch film is above 13 MPa, and the maximum degradation temperature is 87.2°.

[0025] After adopting the above method, the present invention has the following advantages:

[0026] This invention significantly enhances the mechanical and barrier properties of starch films by introducing pullulanase immobilized on cellulose nanofibrils. Furthermore, the innovative addition of curcumin, a pH-sensitive natural pigment, enables the starch film to change color according to changes in ambient pH, thereby enabling intelligent responsiveness for real-time monitoring of food freshness and spoilage. This innovation not only enhances the basic performance of starch films but also provides a new solution for the food packaging industry, demonstrating the broad application prospects of environmentally friendly and biodegradable packaging materials in the field of intelligent monitoring.

[0027] The present invention adds curcumin to the starch film, which can significantly change the color of the starch film from white transparent to yellow transparent film, and the tensile strength, contact angle, and maximum degradation temperature are increased from 9.29MPa, 66.3°, and 314°C to 13.41MPa, 87.2°, and 340.5°C, respectively. The barrier performance is also improved, from 6.23×10 -12 g·cm / Pa·s·cm 2 Reduced to 4.78×10 -12 g·cm / cm 2 ·Pa·s. The curcumin composite film is sensitive to different concentrations of ammonia, producing a distinct color change. Considering the antioxidant properties of curcumin, the composite film has the potential to preserve pork.

[0028] The above summary is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present invention will be readily apparent by reference to the accompanying drawings and the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or technical descriptions. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 is a graph of elongation at break and tensile strength of the present invention;

[0031] Figure 2 Schematic diagram of the starch film of the present invention in ammonia water with different concentrations;

[0032] Figure 3 is a schematic diagram of pork spoilage according to the present invention; Figure 4 1 is a transmission and exposure curve diagram of the starch film of the present invention with Cur added; Figure 5 is a graph showing the strength of the starch film of the present invention with Cur added; Figure 6 are plan and cross-sectional views of the present invention; Figure 7 It is a graph of elongation at break and tensile strength of Cur added in the present invention; Figure 8 It is the TG thermogravimetric curve diagram of the present invention; Figure 9 is a graph of light transmittance of the present invention; Figure 10 is a histogram of the water vapor permeability coefficient of the present invention; Figure 11 Schematic diagram of the contact angle of the present invention; Figure 12 is a color schematic diagram of the film of the present invention; Figure 13 This is a test chart of oil resistance of the present invention; Figure 14 This is a diagram showing the color change of the starch film on the surface of pork according to the present invention. DETAILED DESCRIPTION

[0033] Specific embodiments of the present invention will now be mentioned in detail. Although the present invention is described in conjunction with these specific embodiments, it should be appreciated that the present invention is not intended to be limited to these specific embodiments. On the contrary, these embodiments are intended to cover substitutions, changes or equivalent embodiments that may be included in the spirit and scope of the invention defined by the claims. In the following description, a large amount of specific details are set forth to provide a comprehensive understanding of the present invention. The present invention can be implemented without some or all of these specific details. In other cases, in order not to make the present invention unnecessarily obscure, well-known process operations are not described in detail.

[0034] When used in conjunction with "including," "methods comprising," or similar language in this specification and the appended claims, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0035] The present invention will be described in further detail below in conjunction with the full text.

[0036] Combined with attachment Figures 1-14 A method for preparing a starch-based film with excellent mechanical properties and pH responsiveness comprises the following steps:

[0037] S1. Extrusion treatment:

[0038] The absolute dry starch was mixed evenly using a material mixer, which was divided into five heating zones, namely 50°C, 65°C, 85°C, 100°C and 95°C. The extruded product was immediately freeze-dried and then crushed and sieved for later use;

[0039] S2. Preparation of pectin solution:

[0040] Prepare a standard solution with a pectin content of 60 mg / mL, add distilled water to make up to 100 mL, add 5.0 mL of sulfuric acid / sodium tetraborate solution after ice bath treatment, vortex mix thoroughly, heat in a boiling water bath, and cool to room temperature to obtain a pectin solution;

[0041] S3. Preparation of cellulose nanofibril-immobilized pullulanase:

[0042] CNF (1.0%-10% of the mass of absolute dry starch) and pullulanase (1U-10U per gram of absolute dry starch) are mixed, and the mixture is adjusted to pH 6 using phosphate buffer. The pH-adjusted mixture is shaken at a constant speed of 100-300 rpm in a constant temperature air bath shaker at 30°C for 1-3 hours to complete the immobilization of pullulanase on the cellulose nanofibrils, thereby obtaining a Pul@CNF complex.

[0043] S4, preparation of curcumin-containing starch solution:

[0044] Add 10 ml of 95% ethanol solution to each beaker, add 1-9% curcumin powder, and stir slowly with a glass rod to uniformly disperse the curcumin in the ethanol to obtain a curcumin-ethanol solution;

[0045] S5. Cellulose nanofibril immobilized pullulanase system enzymatically decomposes starch and adds tannic acid:

[0046] Take the absolutely dry starch in S1 and place it in a 250ml three-necked flask or round-bottom flask, add 50ml of distilled water to the flask, and place the flask in a 38℃ water bath. Stir slowly to fully disperse the starch and continue stirring for 5 minutes. Add the prepared Pul@CNF and pectin solution to the dispersed starch solution, and add water to a total volume of 100ml. Add the prepared curcumin-ethanol solution to the above solution respectively, continue stirring for 10 minutes, and heat to 95℃ at a rate of 1℃ / min. When the temperature When the temperature reaches 95°C, glycerol accounting for 40% of the absolute dry starch mass is added to the solution, and the solution is kept warm for 30 minutes while stirring. After the stirring is completed, the bubbles are removed from the obtained starch solution, and the starch solution is evenly spread onto an acrylic plate by a casting method. The acrylic plate with the starch solution spread is placed in a 50°C oven and dried for 8 hours to obtain a composite starch film containing curcumin. After drying, the composite starch film is torn off from the acrylic plate and stored at a temperature of 25°C and a relative humidity of 50% for 48 hours for subsequent use.

[0047] The feed rate of the material mixer is 5-15 kg / h, and the screw speed is 10-20 rpm.

[0048] The mass ratio of the pectin solution to the composite starch film is 1:9.

[0049] The pectin is one or more combinations of xanthan gum, guar gum and sodium carboxymethyl cellulose.

[0050] The product obtained by extrusion in step S1 is immediately freeze-dried and then crushed and sieved to 80-100 mesh for later use.

[0051] In step S2, vortex mix thoroughly and heat in a boiling water bath for 8-12 minutes.

[0052] In step S1, the absolutely dry starch enters the five heating zones of the material mixer in sequence, and the mixing time is 5 min, 6 min, 4 min, 3 min and 3 min.

[0053] The tensile strength of the composite starch film is above 13 MPa, and the maximum degradation temperature is 87.2°.

[0054] During the preparation process, the starch-based film is mixed with glycerin and cast using a solution casting method to further enhance its performance. Physical or chemical modification can improve the barrier properties and mechanical resistance of starch-based films, thereby enhancing their antiseptic properties. These films have been used in applications such as fruit coating, tomato preservation, and fresh pork packaging, demonstrating excellent mechanical properties and water resistance, while effectively inhibiting bacterial growth.

[0055] When implemented, the present invention not only improves the stability and activity of pullulanase, but also further improves the mechanical properties, barrier properties and biological activity of starch film through the reinforcing effect of nanocellulose and the antioxidant properties of curcumin, providing a multifunctional, environmentally friendly and degradable material option for the food packaging field.

[0056] Example 1:

[0057] A method for preparing a starch-based film with excellent mechanical properties and pH responsiveness comprises the following steps:

[0058] S1. Extrusion treatment:

[0059] Absolutely dry starch was mixed evenly using a material mixer with a feed rate of 10 kg / h and a screw speed of 15 rpm. The material mixer was divided into five heating zones, namely 50°C, 65°C, 85°C, 100°C and 95°C, and the mixing time was 5 min, 6 min, 4 min, 3 min and 3 min. The extruded product was immediately freeze-dried and then crushed and sieved through 100 mesh for later use;

[0060] S2. Preparation of pectin solution:

[0061] Prepare a standard solution of sodium carboxymethyl cellulose with a content of 60 mg / mL, add distilled water to make up to 100 mL, add 5.0 mL of sulfuric acid / sodium tetraborate solution after ice bath treatment, vortex mix thoroughly, heat in a boiling water bath for 8-12 minutes, and cool to room temperature to obtain a pectin solution;

[0062] S3. Preparation of cellulose nanofibril-immobilized pullulanase:

[0063] CNF (1.5% of the mass of absolute dry starch) and pullulanase (2 U per gram of absolute dry starch) were mixed, and the mixture was adjusted to pH 6 using phosphate buffer. The pH-adjusted mixture was shaken at 150 rpm in a constant temperature air bath shaker at 30°C for 2 hours to complete the immobilization of pullulanase on the cellulose nanofibrils, thereby obtaining a Pul@CNF complex.

[0064] S4, preparation of curcumin-containing starch solution:

[0065] Add 10 ml of 95% ethanol solution to each beaker, add 7% curcumin powder, and stir slowly with a glass rod to uniformly disperse the curcumin in the ethanol to obtain a curcumin-ethanol solution;

[0066] S5. Cellulose nanofibril immobilized pullulanase system enzymatically decomposes starch and adds tannic acid:

[0067] Take the absolutely dry starch in S1 and place it in a 250ml three-necked flask or round-bottom flask, add 50ml of distilled water to the flask, and place the flask in a 38℃ water bath. Stir slowly to fully disperse the starch and continue stirring for 5 minutes. Add the prepared Pul@CNF and pectin solution to the dispersed starch solution, and add water to a total volume of 100ml. Add the prepared curcumin-ethanol solution to the above solution respectively, continue stirring for 10 minutes, and heat to 95℃ at a rate of 1℃ / min. When the temperature When the temperature reaches 95°C, glycerol accounting for 40% of the absolute dry starch mass is added to the solution, and the solution is kept warm for 30 minutes while stirring. After the stirring is completed, the bubbles are removed from the obtained starch solution, and the starch solution is evenly spread onto an acrylic plate by a casting method. The acrylic plate with the starch solution spread is placed in a 50°C oven and dried for 8 hours to obtain a composite starch film containing curcumin. After drying, the composite starch film is torn off from the acrylic plate and stored at a temperature of 25°C and a relative humidity of 50% for 48 hours for subsequent use.

[0068] Comparative Example:

[0069] A control group was prepared according to the scheme of Example 1, wherein the control group did not add pectin solution and curcumin starch solution, and was not subjected to extrusion treatment. The steps were the same as above, and the two groups of starch films were named 7% Cur (7% Cur / Pul@CNF-StF) and 0% Cur, respectively.

[0070] like Figure 1 As shown, the corn starch film was treated according to ASTM D882-91 standard (ASTM, 2003). After equilibration for 24 hours in a 50% RH environment, the film was cut into rectangular specimens of 100 mm × 20 mm. The film thickness was measured using a handheld digital micrometer with an accuracy of 0.0001 mm. The samples were tensile tested using an automatic tensile testing machine at a speed of 50 mm / min. 10 positions were randomly selected for measurement in each group and the average was calculated. The test was repeated at least 5 times for each sample, and the elongation at break (EAB, %) and tensile strength (TS, MPa) were recorded.

[0071]

[0072] Where: Fmax is the maximum load; S is the initial cross-sectional area; L0 is the initial length of the sample; ΔL is the stretched length of the film.

[0073] Example 2:

[0074] Effect of ammonia on curcumin starch film, such as Figure 2As shown, the starch film containing 7% curcumin is cut into a square of 50mm × 50mm, and a plastic bottle that can accommodate 100ml of liquid is prepared. Subsequently, 20ml of ammonia water of different concentrations (respectively 2%, 4%, 6%, 8%, 10%) is added to each bottle. Afterwards, each bottle mouth is covered with the starch film cut and fastened with a rubber band to ensure sealing. All plastic bottles are placed under constant environmental conditions (23°C, 50%RH), and the color change of the starch film after 20 minutes is observed and recorded.

[0075] Example 3:

[0076] Application as an indicator of pork spoilage, e.g. Figure 3 As shown, a 7% Cur film was applied to pork to evaluate its freshness. Pork chunks weighing 10 g were placed in sterilized Petri dishes (15 cm diameter) and covered with Cur. The dishes were then sealed with polyethylene film and placed in a BIC250 artificial climate incubator (Shanghai, China) at 35°C and 75% RH. The samples were observed every 24 hours.

[0077] This study prepared curcumin / cellulose nanofibril-immobilized pullulanase starch films by adding curcumin to cellulose nanofibril-immobilized pullulanase. The films were compared for physical properties such as tensile strength, elongation at break, light transmittance, and water vapor permeability. The color response of the curcumin starch films at different ammonia concentrations was also recorded. These curcumin starch films can be used for intelligent monitoring of pork spoilage.

[0078] Experimental materials and reagents:

[0079] The raw materials used in the present invention are mainly ordinary corn starch provided by Zhejiang Jingxing Company, with a water content of 12.2%. Cellulose nanofibrils (CNF: length 100-5000nm; width 1-20nm; concentration 0.8%; cationic charge, 0.2-1.5mmol / g) provided by Zhejiang Jinjiahao Green Nanomaterial Co., Ltd. The main reagents used in the present invention are shown in Table 1

[0080] Table 1 Experimental reagents

[0081] Reagent name Properties / Specifications Production Company Pullulanase (Pul) 2000U / g (liquid) Shanghai MacLean Biochemical Technology Co., Ltd. Glycerol 99% Tianjin Jiangtian Chemical Technology Co., Ltd. Acetic acid-sodium acetate buffer solution —— Laboratory-made ethanol 95% Tianjin Jiangtian Chemical Technology Co., Ltd. Curcumin (Cur) 25g Tianjin Solomon Biotechnology Co., Ltd. pork —— Meituan Youxuan (Purchase) ammonia Chromatographic grade, ≥25% Shanghai Aladdin Biochemical Technology Co., Ltd.

[0082] Table 2 Main instruments and equipment used in the experiment

[0083]

[0084]

[0085] Preparation of curcumin-coated starch films

[0086] Take five beakers, add 10ml of 95% ethanol solution to each beaker, and then add curcumin to each beaker in a ratio of 0%, 3%, 5%, 7%, and 9% (relative to the absolute dry starch mass). Use a glass rod to stir slowly to ensure that curcumin is evenly dispersed in ethanol. Afterwards, the configured curcumin-ethanol solution is added to the film-forming solution after the cellulose nanofibril immobilized pullulanase enzymatic hydrolysis of starch (the film-forming solution has been raised to 95°C and no glycerol is added). After keeping warm at 95°C for 30 minutes, 40% glycerol is added to each beaker and continued to keep warm for 30 minutes while stirring. After stirring, remove the bubbles in the starch solution, use a casting method to evenly spread the starch solution on an acrylic plate, and then put it into an oven set at 50°C for drying for 8 hours. After drying, gently remove the starch film from the acrylic plate and store it for 48 hours at a temperature of 25°C and a relative humidity (RH) of 50% for subsequent use. According to the addition ratio of curcumin, the five starch films were named 0% Cur (Pul@CNF-StF), 3% Cur (3% Cur / Pul@CNF-StF), 5% Cur (5% Cur / Pul@CNF-StF), 7% Cur (7% Cur / Pul@CNF-StF) and 9% Cur (7% Cur / Pul@CNF-StF).

[0087] Colorimeter measurement:

[0088] The color of the curcumin starch film was measured using a portable spectrophotometer colorimeter to obtain the L, A, and B parameters. The total color difference was calculated using the equation: white plate values ​​L: 97, A: 1.21, B: 3.85.

[0089]

[0090] L, A, and B—where L represents white light; and A and B represent the color values ​​of red-green and yellow-blue, respectively. Total color difference (ΔE).

[0091] Effect of ammonia on curcumin starch film:

[0092] Cut the starch film containing 7% curcumin into a square of 50mm × 50mm, and prepare a plastic bottle that can accommodate 100ml of liquid. Subsequently, 20ml of ammonia water of different concentrations (respectively 2%, 4%, 6%, 8%, 10%) was added to each bottle. Afterwards, each bottle mouth was covered with the cut starch film and fastened with a rubber band to ensure sealing. All plastic bottles were placed under constant environmental conditions (23°C, 50%RH), and the color change of the starch film after 20 minutes was observed and recorded.

[0093] Oil resistance level test:

[0094] According to the GB / T7714-2015 standard, the oil resistance of starch film is evaluated. Before the test, the starch film sample is cut to the specified size and ensured to be flat. The experiment is carried out in a temperature and humidity controlled environment, set at 23±2℃ and 50±5%RH. During the test, a specified volume of oil is dropped onto the starch film from a height of 25cm, and it is observed whether it penetrates quickly. After 15s, check and record the diameter of the oil stain on the absorbent paper, and take a photo for backup. According to the size of the oil stain diameter, it is evaluated against the grade table in the standard. The grade range is usually from grade 1 (no oil resistance) to grade 12 (excellent oil resistance).

[0095] Application as an indicator of pork spoilage:

[0096] Pork freshness was assessed using a 7% Cur film applied to it. 10g of pork chunks were placed in a sterilized Petri dish (15cm diameter) and covered with Cur. The dish was then sealed with polyethylene film and placed in a BIC250 artificial climate incubator (Shanghai, China) at 35°C and 75% RH. The freshness was observed every 24 hours.

[0097] Results and Analysis

[0098] Colorimeter test analysis

[0099] Analysis of Table 3 shows that after adding curcumin to the starch film, the film becomes yellow and transparent, and the color deepens as the curcumin content increases. The starch film with added curcumin still has a certain degree of transparency, and the text on the back can be seen through the film. The curcumin starch film appears yellow, and curcumin itself is a natural pigment that appears yellow. When curcumin is added to the starch film, it is evenly dispersed in the starch matrix, making the entire film appear yellow. The yellow color of curcumin comes from the conjugated double bond system in its molecular structure. This structure can absorb light of a specific wavelength and reflect or emit yellow light, thus the yellow starch film. The addition of curcumin reduces the brightness value (L value) of the starch film and increases the chromaticity value (B value). As the concentration of curcumin increases, the total color difference (ΔE) also increases. Adding Cur to the starch film can change the color of the starch film.

[0100] Table 3 Color parameters of starch films with different curcumin addition amounts

[0101] sample L A B ΔE Whiteboard 97 1.21 3.85 Curcumin 3% 83.5±0.31 -2.47±0.58 26.92±0.21 25.43±0.35 Curcumin 5% 81.24±0.15 -6.3±0.75 49.57±0.85 47.77±0.35 Curcumin 7% 80.83±0.46 -6.65±0.65 54.33±0.54 52.48±0.74 Curcumin 9% 75.72±0.45 12.71±0.45 61.89±0.78 62.4665

[0102] Attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) analysis

[0103] like Figure 4After Cur is added to the starch film (see a), no chemical bonds of Cur are observed, except for a slight change in peak intensity. Its infrared signal may be masked by the starch signal, making it difficult to clearly detect the characteristic peak of Cur. Therefore, an infrared deconvolution image was used to understand the effect of curcumin on the short-range order of the starch sample.

[0104] From the analysis of Table 4, we can see that at 1046cm -1 / 1022cm -1 The ratio of the ordered structure gradually increased with the addition of curcumin (from 0.581 to 0.710), indicating that the addition of curcumin promoted the formation of short-range structures in the starch film. The addition of curcumin formed hydrogen bonds or other types of interactions with starch molecules, which promoted the orderly arrangement of starch molecules, thereby increasing the short-range order. At 9% curcumin content, the ratio of the ordered structure decreased slightly (0.562), which may indicate that the aggregation of curcumin at too high a concentration interfered with the formation of the ordered structure of starch.

[0105] Table 4 Infrared spectra of starch film after deconvolution at 1046 cm -1 / 1022cm -1 Absorbance ratio

[0106]

[0107] Wide-angle X-ray diffraction (XRD) pattern analysis

[0108] like Figure 5 As shown in the figure, after adding Cur to the starch film, the 15° peak in the control group disappeared, and a new peak appeared at 17.25°, which became stronger with the increase of curcumin. The peak at 15° disappeared after adding curcumin. This may be because curcumin interacts with starch molecules, changes the crystal structure of starch, causes the original crystal phase to disappear and induces the formation of a new crystal phase. , and no peak at 15° can be produced. Usually, the XRD diffraction of Cur has peaks at 8.84°, 12.10°, 14.39°, 17.20°, 23.33°, 24.50, 25.52° and 28.87°, indicating that the new peak at 17.25° is related to curcumin. Curcumin itself is highly crystalline, and when it is combined with starch, it may retain its crystalline properties. Adding Cur to the starch film resulted in a distinct diffraction peak at 17.25°, indicating good compatibility between curcumin and starch, allowing it to be evenly dispersed in the starch matrix. The good dispersibility of curcumin in starch helps form an ordered crystalline structure in the starch film, thereby improving the film's crystallinity.

[0109] As shown in Table 5, the crystallinity of the composite material increases with increasing Cur content, reaching a peak of 33.25% when the Cur content reaches 7%. This indicates that the addition of curcumin can promote the formation of crystalline regions in the starch film. This may be related to the crystallinity of curcumin itself.

[0110] Table 5 Curcumin starch films with different curcumin addition amounts

[0111]

[0112]

[0113] Scanning electron microscopy (SEM) observation:

[0114] Figure 6 As shown in the plan view, the surfaces of the starch film without curcumin and the starch film with a small amount of curcumin (0%-5%) are smooth and free of particles. This shows that curcumin has good compatibility with starch and cellulose. When the curcumin addition amount is 7%, the surface of the starch film begins to become rough, and when the curcumin addition amount is 9%. Excessive curcumin agglomerates in the starch solution, eventually resulting in a rough surface of the starch film (SEM plan view of adding 9% curcumin). On the other hand, too much curcumin cannot dissolve in starch, and it also affects the distribution of nano-CNFs, causing CNFs to agglomerate (similar to SEM, when 2.5% CNFs are added, agglomeration occurs, resulting in a rough surface), making the surface of the starch film rough.

[0115] Figure 6 As shown in the cross-sectional view, the starch film has a slightly layered structure. This is the structure of the interaction between CNF and amylose. CNF forms a tight structure with the long and short starch molecular chains in the starch, thus producing a microlayer structure in the cross-section. When the addition amount of curcumin is ≥7%, a bulge appears on the cross-section. When the addition amount is 9%, the bulge is more obvious. This bulge may be caused by the excessive curcumin forming some irregular aggregates, which accumulate in the starch, resulting in poor starch compatibility and affecting the structure of the starch film. This result shows that Cur has good compatibility with starch at low concentrations.

[0116] Mechanical properties analysis

[0117] Table 6 shows that the tensile strength of the starch film significantly increases with increasing Cur addition. From 9.29 MPa at 0% Cur to 9.79 MPa at 3% Cur, to 12.44 MPa at 5% Cur, and to 13.41 MPa at 7% Cur, it can be seen that the addition of Cur significantly enhances the tensile strength of the starch film. This may be because hydrogen bonds are formed between Cur molecules and starch molecules, enhancing intermolecular interactions and thus increasing the tensile strength of the film. The elongation at break of the starch film significantly decreases. From 38.56% at 0% Cur to 20.19% at 3% Cur, to 11.68% at 5% Cur, and to 10.02% at 7% Cur, it can be seen that the addition of Cur reduces the elongation at break of the film. This may be because the addition of Cur enhances intermolecular interactions, making the film more susceptible to brittle fracture when subjected to external forces, rather than absorbing energy through deformation.

[0118] Table 6 Mechanical properties of starch films with different curcumin addition amounts

[0119] sample Thickness (mm) Tensile strength (MPa) Elongation at break (%) 0%Cur 0.110 9.29 38.56 3%Cur 0.120 9.79 20.19 5%Cur 0.110 12.44 11.68 7%Cur 0.125 13.41 10.02 9%Cur 0.117 9.73 20.87

[0120] like Figure 7 As shown in the figure, when the Cur addition amount is 7%, the tensile strength of the composite material reaches a maximum value of 15.51MPa. However, when the Cur content exceeds 7%, the tensile strength begins to decrease. This is because the excess curcumin is unevenly distributed in the material and aggregates, which weakens the surface interaction between curcumin and starch, and thus interferes with the connection between starch and cellulose nanofibrils. Although the tensile strength increases, the elongation at break continues to decrease. This is because the tight intermolecular binding makes the molecular chains of starch unable to move, resulting in a decrease in elongation at break. Controlling the amount of curcumin added is crucial to optimizing the mechanical properties of starch films. The significant increase in the rigidity of the starch film will lead to a loss of its elastic properties.

[0121] Thermogravimetric (TG) analysis

[0122] like Figure 8 Figure (a) shows the TG thermogravimetric curves of Cur / Pul@CNF films with varying amounts of Cur added. All films exhibited a three-step thermal degradation process. The third stage, at 290°C-600°C, primarily involved starch degradation. The starch films without Cur added experienced the most weight loss compared to those with Cur added, demonstrating that curcumin stabilizes the starch films.

[0123] In order to fully understand the thermal behavior of different composite films, the first-order derivative DTG curve was calculated and the results were shown in Figure 2. Figure 5-8b. As shown in Figure b, the maximum degradation temperature of the starch film without Cur is 314°C, while the degradation temperature of the starch film with Cur is 340.5°C. The control group of starch film with Cur is 26.5°C higher, indicating enhanced thermal stability. This is due to the high crystallinity of curcumin itself, and the fact that the phenolic hydroxyl groups of Cur in starch can form stable hydrogen bonds with the hydroxyl groups in CNF and starch molecules, which improves the thermal stability of the starch film. This enhanced interaction can improve the ability of the starch film to resist thermal degradation, thereby increasing its thermal stability. This shows that adding Cur to the starch film can effectively improve the thermal stability of the starch film.

[0124] Transmittance analysis:

[0125] like Figure 9 As shown, when Cur is added to a starch film, the film's light transmittance gradually decreases with increasing curcumin addition. Because curcumin itself is a naturally active ingredient with a distinct color, its incorporation into a starch matrix significantly alters the film's color and light transmittance. Uneven dispersion of curcumin molecules within the starch film also causes light to scatter as it passes through the film, reducing light transmittance. Adding Cur to a starch film reduces light transmittance.

[0126] Water vapor transmission coefficient analysis:

[0127] like Figure 10 As shown in Figure 2, with the addition of curcumin to the starch film, the water vapor permeability coefficient gradually decreases. When the addition amount is 7%, the water vapor permeability coefficient of the starch film is the minimum, which is 4.78×10 -12 g·cm / cm 2 ·Pa·s. When the addition amount of curcumin exceeds 7%, the water vapor permeability coefficient begins to decrease. When an appropriate amount of Cur is added, the water vapor permeability coefficient decreases. This is because the strong hydrogen bonding between Cur, CNF, and starch molecules increases the density of the membrane, making it difficult for water molecules to pass through the polymer matrix. Secondly, the highly hydrophobic curcumin molecules hinder the interaction between water and starch, thereby significantly reducing the water vapor permeability coefficient. When the water vapor permeability coefficient increases, due to the uneven distribution of excessive curcumin and the aggregation of curcumin, defects appear between starch and starch, between starch and CNF, and between curcumin and CNF, which increases the permeability of the starch membrane. Curcumin is observed to have similar hydrophobicity.

[0128] Contact angle analysis:

[0129] like Figure 11As shown in the figure, the starch film with curcumin exhibits a higher contact angle than the starch film without curcumin. Furthermore, as the amount of curcumin added increases, the contact angle of the starch film gradually increases. Curcumin molecules themselves are insoluble in water and are hydrophobic, repelling water molecules. When curcumin is added to the starch film, the hydrophobic molecules tend to gather on the surface of the film, forming a relatively hydrophobic outer layer. The presence of this hydrophobic outer layer causes water droplets to form a larger contact angle on the film surface. This indicates that the starch film with curcumin added has good hydrophobicity.

[0130] Effect of ammonia on curcumin film:

[0131] from Figure 12 It was observed that when 7% Cur / Pul@CNF-StF was added to different concentrations of ammonia, the color of the film changed from yellow to brown-red, which had a relatively obvious warning effect. From 0% to 10% ammonia concentration, the color gradually changed from yellow to a deeper brown-red. This is because the volatilization of alkaline ammonia interacts with the phenolic hydroxyl groups in the molecular structure of curcumin, generating phenolate anions and causing the color change. In an alkaline environment, the hydroxyl groups at both ends of the curcumin molecule lose protons, causing the electron cloud to deviate, thereby changing the absorption spectrum of the molecule. Curcumin added to the starch film has the ability to respond to pH, allowing the starch film to be used as a pH-responsive intelligent packaging film.

[0132] Oil proof grade analysis:

[0133] like Figure 13 As shown, the starch film performed well in oil-repellency tests, achieving an oil-repellency rating of 11 or higher. This is because the starch molecules and CNFs in the starch film contain a large number of hydroxyl groups, which have poor compatibility with oils and fats. The hydroxyl groups of the starch molecules and CNFs form an oil-repellent interface, effectively preventing oil molecules from penetrating through the pores of the film. The addition of curcumin further enhances the oil-repellency of the composite film, achieving an outstanding rating of 12. This is likely due to the uniform distribution of curcumin molecules in the film, which enhances its barrier ability to oils. Therefore, this composite starch film exhibits excellent oil-repellency and shows broad application prospects in the packaging of oily foods.

[0134] Application as an indicator of pork spoilage:

[0135] like Figure 14As shown in Figure 2, after coating pork with a curcumin-added starch film, a noticeable color change can be observed on the surface of the pork. As shown in Figure c, 24 hours after coating, red spots gradually appeared on the originally yellow starch film. Over time, as shown in Figure f, at 48 hours, the red areas on the starch film further expanded and deepened. This is because the spoilage of pork produces volatile basic nitrogen (alkaline oxygen-containing substances) and the pH of the pork also changes. These changes cause the curcumin in the curcumin-added starch film to change color, from yellow to red. This phenomenon clearly demonstrates that the curcumin-added starch exhibits a high sensitivity to changes in pork freshness. By visually observing the color change of the film, the freshness of food can be easily assessed. This method is not only simple and practical, but also provides an effective visual monitoring method for food safety and quality control.

[0136] The present invention adds curcumin to cellulose nanofibril-immobilized pullulanase to prepare curcumin / cellulose nanofibril-immobilized pullulanase starch film (Cur / Pul@CNF-StF). Appropriate addition of curcumin can improve the performance of the starch film.

[0137] Adding 7% curcumin to starch film can significantly change the color of the starch film from white transparent to yellow transparent film, and the tensile strength, contact angle and maximum degradation temperature are increased from 9.29MPa, 66.3° and 314°C to 13.41MPa, 87.2° and 340.5°C respectively. The barrier properties are also improved from 6.23×10 -12 g·cm / Pa·s·cm 2 Reduced to 4.78×10 -12 g·cm / cm 2 ·Pa·s. The curcumin composite film is sensitive to different concentrations of ammonia, producing a distinct color change. Considering the antioxidant properties of curcumin, the composite film has the potential to preserve pork.

[0138] The present invention and its embodiments are described above. This description is not restrictive. What is shown in the full text is only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if a person skilled in the art is inspired by this and, without departing from the purpose of the present invention, designs a structure and embodiment similar to this technical solution without creatively designing, they shall all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a starch-based film with excellent mechanical properties and pH responsiveness, characterized in that: The following steps are involved: S1. Extrusion treatment: The absolutely dry starch is mixed evenly using a material mixer, which is divided into five heating zones, namely 50°C, 65°C, 85°C, 100°C and 95°C. The product obtained by extrusion is immediately freeze-dried, crushed and sieved for later use; S2. Preparation of pectin solution: Prepare a standard solution with a pectin content of 60 mg / mL, add distilled water to make up to 100 mL, add 5.0 mL of sulfuric acid / sodium tetraborate solution after ice bath treatment, vortex mix evenly, heat in a boiling water bath, and cool to room temperature to obtain a pectin solution; S3. Preparation of cellulose nanofibril immobilized pullulanase: Take CNF, the mass of which is 1.0%-10% of the mass of absolute dry starch, take pullulanase, the amount of which is 1U-10U per gram of absolute dry starch, mix CNF and pullulanase, and adjust the mixture with phosphate buffer to a pH value of 6, and shake the mixture with the adjusted pH value at a constant speed of 100-300rpm in a constant temperature air bath shaker at 30°C for 1-3 hours to complete the immobilization of pullulanase on cellulose nanofibrils, and obtain Pul@CNF composite; S4, preparation of curcumin-containing starch solution: Add 10 ml of 95% ethanol solution to each beaker, add 1-9% curcumin powder, and stir slowly with a glass rod to evenly disperse the curcumin in the ethanol to obtain a curcumin-ethanol solution; S5. Cellulose nanofibril immobilized pullulanase system enzymatically hydrolyzes starch and adds tannic acid: The absolute dry starch in S1 was placed in a 250 ml three-necked flask or round-bottom flask, 50 ml of distilled water was added to the flask, and the flask was placed in a 38 ° C water bath environment, and the starch was fully dispersed by slowly stirring, and the stirring was continued for 5 minutes. The prepared Pul@CNF and pectin solution were added to the dispersed starch solution, and water was added to the total volume of 100 ml. The prepared curcumin-ethanol solution was added to the above solution respectively, and the stirring was continued for 10 minutes. The temperature was raised to 95 ° C at a rate of 1 ° C / min. When the temperature When the temperature reaches 95°C, glycerol accounting for 40% of the absolute dry starch mass is added to the solution, and the solution is kept warm for 30 minutes while stirring. After the stirring is completed, the bubbles are removed from the obtained starch solution, and the starch solution is evenly spread on the acrylic board by a casting method. The acrylic board with the spread starch solution is placed in a 50°C oven and dried for 8 hours to obtain a composite starch film containing curcumin. After drying, the composite starch film is torn off the acrylic board and stored at a temperature of 25°C and a relative humidity of 50% for 48 hours for subsequent use.

2. The method for preparing a starch-based film having excellent mechanical properties and pH responsiveness according to claim 1, characterized in that: The feed rate of the material mixer is 5-15 kg / h, and the screw speed is 10-20 rpm.

3. The method for preparing a starch-based film having excellent mechanical properties and pH responsiveness according to claim 1, characterized in that: The mass ratio of the pectin solution to the composite starch film is 1:

9.

4. The method for preparing a starch-based film having excellent mechanical properties and pH responsiveness according to claim 1, characterized in that: The pectin is one or more combinations of xanthan gum, guar gum and sodium carboxymethyl cellulose.

5. The method for preparing a starch-based film having excellent mechanical properties and pH responsiveness according to claim 1, characterized in that: The product obtained by extrusion in step S1 is freeze-dried immediately, crushed and sieved to 80-100 mesh for later use.

6. The method for preparing a starch-based film having excellent mechanical properties and pH responsiveness according to claim 1, characterized in that: In step S2, vortex mix thoroughly and heat in a boiling water bath for 8-12 min.

7. The method for preparing a starch-based film having excellent mechanical properties and pH responsiveness according to claim 1, characterized in that: In step S1, the absolutely dry starch enters the five heating zones of the material mixer in sequence, and the mixing time is 5 min, 6 min, 4 min, 3 min and 3 min.

8. The method for preparing a starch-based film having excellent mechanical properties and pH responsiveness according to claim 1, characterized in that: The tensile strength of the composite starch film is above 13 Mpa, and the maximum degradation temperature is 87.2°.

Citation Information

Cited By

  • Curcumin nanoemulsion and Nisin-A loaded starch / pectin composite film as well as preparation method and application thereof

    CN120059304A

  • A starch / pectin composite film loaded with curcumin nanoemulsion and nisin-a, and a preparation method and application thereof

    CN120059304B